Literary Journalism in the Face of Global Food Crisis: Techniques on the way out - Gregory Ezeah; Verlumun Celestine Gever (Cхід, 2019)
Over the years, world leaders have continued to troubleshoot approaches to combating hunger. Although the increasing hunger appears to be affecting countries in different continents of the world, African countries and part Asia appear to be most hit. This study examines the nexus between literary journalism and combating the global hunger crisis with specific attention to Nigeria. Specifically, the study examined the extent literary journalism can be deployed to combat hunger, the techniques to deploy in using literary journalism to drive government policies on food sufficiency and encourage public participation in agriculture. Literary journalism, though an emerging field, has the potential of promoting agricultural activities and policies that will lead to eventual food security. Literary journalism presents an opportunity through which agriculture can be developed and food security enhanced. Understanding the approaches and techniques of literary journalism for combating global food crisis is a significant contribution to literature in the following ways: First, it will provide newer insights into the role of literary journalism in agricultural development and food security. In the second place, this study contributes to literature by opening a new vista in the study of literary journalism. The International Food Policy Research Institute in collaboration with the Food and Agriculture Organization in its Global Hunger Index grouped Nigeria among countries with a high level of hunger threat, with an index of 25.5 which was categorized as serious hunger threat. Based on the concept of 'breakable rules' by Mark Kramer, the following characteristics of literary journalism stand out: immersion in the story worlds; developing implicit rules (covenants) on accuracy and sincerity; description mainly about everyday, routine events; development of meaning, based on a consistent reaction of readers. This study raises the following researcher questions: To what extent can literary journalism promote food security? What literary journalism techniques can be used to encourage participation in agriculture? What literary journalism techniques can be used to drive government policies and programs in agriculture? A total of 30 respondents provided narratives on the nexus between literary journalism and food sufficiency. A structured interview guide was used as the instrument for data collection while thematic analysis guide was used to analyze the result of study. The result of the semi-structured interview revealed that literary journalism can aid in combating food crisis globally and in Nigeria in particular to a large extent. It was also found that the techniques to be used for combating food crisis include scene-by scene, infotainment, dialogue, subjectivity and accuracy. During the interview sessions, it was discovered that the respondents reported that literary journalism has not been given its pride of place in Nigeria, unlike other parts of the world like the United States of America where it has been in practice since the 1960s.These results were examined with the framework of ACADA model. The model stands for Assessment, Communication, Analysis Design and Action. The model was developed by the United Nations for International Children Emergency Fund. The implications of these results on food sufficiency and the expansion of literature on literary journalism were also discussed.